Análisis económico de un sistema silvopastoril en el Delta del río Paraná, Argentina - Egolf, Patricia; Benito Amaro, Ignacio; Ravalli, Juan Diego; Gonzalez, Adrian Claudio; Faustino, Laura Ines; Colcombet, Luis (Asociación Argentina de Economía Agraria, 2022)
Ponencia y presentación en diapositivas